Viral Diagnostics and Preventive Techniques in the Era of COVID-19: Role of Nanoparticles - Chakraborty, Debolina; Kumar, Sanjit; Chandrasekaran, N.; Mukherjee, Amitava (Frontiers in Nanotechnology, 2020)
COVID-19 outbreak in the Hubei province of China as of December 2019 has caused massive global fatalities. Recommended preventive strategies that include the use of sanitizers and masks caused a global shortage of protective gear for the frontline health workers who were at a higher risk of infection. Implementing effective containment strategies and promoting large scale diagnosis of the general public thus forms the first line of defense in controlling the spread of the contagion as of now. The understanding of the biological identity of the SARS-CoV-2 virus has helped the researchers figure out the mechanism of infection and also helped them design efficient diagnostic kits. This review primarily provides comprehensive details of the gold standard viral diagnostic methods. With nanoparticles playing a vital role in healthcare platforms, its mode of action against other viruses and its application in COVID-19 has been elaborated. The relevance of incorporating nanoparticles in surface coatings, sanitizers, masks, and air filters have been highlighted. NP-based biosensors that can be utilized as point-of-care tests and multiplexed assay have also been discussed. Considering the ongoing threat, new research studies focus on strategically combining different diagnostic systems to enhance the sensitivity and accuracy of the detection kits. In this regard, the key details of the patents that encompass new methodologies for virus detection have been summarized